Anti-Chinese stigma in the Greater Toronto Area during COVID-19: Aiming the spotlight towards community capacity - Aaida A. Mamuji (Elsevier, 2021)
Due to the geographic origins of the first major outbreak of COVID-19 in Wuhan, China, individuals of Chinese ethnic origin around the world have experienced discrimination, xenophobia, and racism during the pandemic. Discriminatory actions have ranged from outright physical aggression to subtle microaggressions. While reports (both media and academic) have highlighted such incidents, this paper argues that when the conversation starts and stops at the reporting of experiences of stigma, the narrative remains as the victimization of the community. Instead, instances of COVID-19 stigma and discrimination are only one aspect of this story, where other aspects include a deeper understanding of the community itself along with an awareness of the capacity that the Chinese diaspora community brings forward to help overcome COVID-19. We focus our discussion on the Greater Toronto Area (GTA) in Canada, a global urban center that has a sizeable ethnic Chinese diaspora community, and argue that highlighting the early actions that the community took to help broader society in dealing with COVID-19 at the start of the pandemic may help to reframe anti-Chinese stigma during the pandemic. These early actions include physical distancing, mask-wearing, sanitation and advocacy. Findings for this case-study are informed by media monitoring and interviews with 83 individuals identifying as ethnically Chinese living across the GTA.